Privacy, Publicity, and Gender in Amsterdam’s Early Modern Urban Space - Pierik, Bob (Privacy Studies Journal, 2022)
This article considered the layers of publicity and privacy in urban space in Amsterdam through conflicts from notarial depositions. It explores and describes the everyday culture of transparency and its relative openness, in which the practices of movement within, through, and around the house were mediated by gender, class, and materiality. It considers how despite the relative openness of homes, demarcations were not absent in early modern cities, but followed a different spatial logic than we know today. Through the concept of practices of gatekeeping, privacy and publicity are not considered as absolute opposites, but rather as powers that can be at work in the same place, allowing for a more multi-layered perspective on urban space. Through this lens, this article considers different ways in which women and men of different social status claimed and negotiated publicity and privacy in everyday life, on the doorsteps of their houses, in the alleys were they lived and away from their homes. By turning to snapshots of street life, it shows how these negotiations were influenced by both social-cultural attitudes and the materiality of urban life in the form of doors, raised doorsteps and windows. Finally, it considers how although both publicity and privacy were forces at work in the street and in houses, a more complete form of secrecy and privacy required mobilities of a larger scope, as people moved outside the city or at least to its fringes. Behaviour that one wanted to keep secret would, under most circumstances, have required the necessary mobility to stay secret, and the spatial constellation of privacy was often directed outwards rather than inwards.